Measuring the finishing performance of steers and heifers - Langemeier, Michael R.; Jones, R.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined improvements in the finishing performance of steers and heifers from 1990 to 1998 by measuring the rate of technological change. The rates of technological change were 0.58% per year for finishing steers and 1.01% per year for finishing heifers. The relatively higher rate for heifers indicates that technological change over the study period favored the performance of heifers.
Keywords: Beef; Steer finishing; Heifer finishing; Technological change